Blended Teaching Creativity In English Learning for Elementary Schools - Fitriana, Dina (Jurnal Basicedu, 2022)
Destination from study this is for knowing how creativity teaching blended on learning language English for Elementary School . Method research used in study this is method descriptive type studies literature , data collection was carried out through studies literature with use the best reference with creativity teaching blended on learning language English for Elementary School . H result study show that creativity teaching blended on learning language English for Suitable Elementary School is  type flex blended learning , besides that system management learning with neat and good in blended teaching on learning language English for Elementary school is also important. The results of the study also show that teaching blended on eye lesson  language English is a must as one adjustment after the Covid 19 pandemic, even though at first not yet used to however moment this Becomes a necessity . Article conclusion this is creativity teaching blended on teaching language English for Elementary School is well and so that all walk fluent teacher is the most important key.